Business Ethics, Internal Control, and Cybersecurity in Foreign Exchange Transactions: Empirical Evidence from Indonesia - Misni Erawati; Ratih Kusumastuti; Rahayu; Lutfi; Derist Touriano; Afriantoni (The Indonesian Accounting Review, 2026)
This study examines the relationship between business ethics, internal controls, cybersecurity, and foreign exchange transactions in Indonesia. Cybersecurity is positioned as a mediating mechanism that links governance-related factors to the success of foreign exchange transactions in the banking sector. Using a quantitative survey approach, data were collected from directors and managers of foreign exchange companies affiliated with the Indonesian Foreign Exchange Dealers Association (APVA) that were accessible during the data collection period. A total of 176 questionnaires were distributed, and 121 usable responses were analyzed using path analysis in the SPSS. The results show that business ethics positively and significantly affect cybersecurity, indicating that ethical values, such as integrity, transparency, accountability, and compliance, support stronger cybersecurity practices. Internal control also has a positive and significant effect on cybersecurity, suggesting that control mechanisms contribute to the protection of digital financial transactions. Furthermore, cybersecurity has a positive and significant effect on foreign exchange transactions. However, business ethics and internal controls do not have significant direct effects on foreign exchange transactions, indicating that their contributions operate indirectly through the aspect of cybersecurity. These findings highlight cybersecurity as a strategic governance capability that connects ethical conduct and internal control with transaction reliability, data integrity, and stakeholder trust.